2016
DOI: 10.1590/s0102-865020160050000002
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin and biphasic calcium phosphate affects bone formation in critical-sized rat calvarial defects

Abstract: PURPOSE:To investigate the effects of locally applied simvastatin plus biphasic calcium phosphate (BoneCeramic ® ) or collagen sponge on bone formation in critical-sized bone defects. METHODS:Thirty defects of 5mm in diameter were created bilaterally with a trephine bur in the calvariae of fifteen Wistar rats. The defects were divided into five groups: group 1 -control, no treatment; group 2 (BoneCeramic ® ); group 3 (BoneCeramic ® + 0.1mg simvastatin); group 4 (collagen sponge); and group 5 (collagen sponge +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Recent studies have investigated the effect of the local application of simvastatin associated with different carriers such as methylcellulose gel [25,37], inorganic bovine bone graft, hydroxiapatite combined with calcium sulphate [38], polylactic acid/polyglycolic acid copolymer [39], calcium sulphate [36,40], lyophilized sponge [41], collagen sponge [42] and gelatin sponge [22,43]. However, there is no consensus about an ideal carrier of the drug for bone defects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have investigated the effect of the local application of simvastatin associated with different carriers such as methylcellulose gel [25,37], inorganic bovine bone graft, hydroxiapatite combined with calcium sulphate [38], polylactic acid/polyglycolic acid copolymer [39], calcium sulphate [36,40], lyophilized sponge [41], collagen sponge [42] and gelatin sponge [22,43]. However, there is no consensus about an ideal carrier of the drug for bone defects.…”
Section: Resultsmentioning
confidence: 99%
“…LED therapy provides positive effects in several procedures. LED arrays do not generate heat during the therapy, therefore thermal injury is not expected, unlike with LLLs [42]. Furthermore, LED therapy can be arranged by flat arrays allowing treatment of larger surface with lower cost compared to LLL therapy [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…CSD is “the smallest intrabony wound which does not heal spontaneously” ( 24 ). The proper CSD size for evaluation of bone regenerative biomaterials in a rat calvarial defect model has not been determined and full-thickness CSDs of 5mm-diameter ( 21 , 23 , 25 - 29 ) or 8mm-diameter ( 22 , 30 - 32 ) have been used. Full-thickness 5mm-diameter defects simplify surgical procedure and allow the creation of bilateral defects, reducing rats’ mortality and morbidity ( 21 , 33 ), and consequently the total number of animals that are required ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Histomorphometrical analysis is the gold standard for the assessment of new bone formation in rat calvarial CSDs ( 21 , 22 , 29 ). In this study, digital image analysis allowed an objective comparison of new bone formation among experimental and control CSDs, as estimated by the surface of the newly formed bone and number of osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were housed in groups of five per cage in standard conditions with food and water ad libitum at room temperature with a 12-hour light/dark cycle (06:00 to 18:00 h). Female rats were used in this experiment because previous work from our research group showed very good response stability in the results obtained, although hormonal interferences were not considered 25 . The ARRIVE protocol guidelines was followed in this study.…”
Section: ■ Methodsmentioning
confidence: 99%